Assessment of the Mate Retention Inventory-Short Form Using Item Response Theory. (October 2021) - Nebl, Patrick J.; McCoy, Mark G.; Foster, Garett C.; Zickar, Michael J.
The mate retention inventory (MRI) has been a valuable tool in the field of evolutionary psychology for the past 30 years. The goal of the current research is to subject the MRI to rigorous psychometric analysis using item response theory to answer three broad questions. Do the individual items of the MRI fit the scale well? Does the overall function of the MRI match what is predicted? Finally, do men and women respond similarly to the MRI? Using a graded response model, it was found that all but two of the items fit acceptable model patterns. Test information function analysis found that the scale acceptably captures individual differences for participants with a high degree of mate retention but the scale is lacking in capturing information from participants with a low degree of mate retention. Finally, discriminate item function analysis reveals that the MRI is better at assessing male than female participants, indicating that the scale may not be the best indicator of female behavior in a relationship. Overall, we conclude that the MRI is a good scale, especially for assessing male behavior, but it could be improved for assessing female behavior and individuals lower on overall mate retention behavior. It is suggested that this paper be used as a framework for how the newest psychometrics techniques can be applied in order to create more robust and valid measures in the field of evolutionary psychology.